Content Knowledge Among Prospective English Teacher in Developing Lesson Plans: A Systematic Review - Rahmawati, Aprilia Afifatur; Anjaniputra, Agung Ginanjar (International Journal of Learning and Instruction (IJLI), 2025)
This study conducted a literature review of the role of knowledge teachers using the PRISMA 2020 statement guidelines. The 311 articles were initialed from Scopus and ERIC databases and published from 2006 to 2025. The samples include prospective teachers' content knowledge divided into inclusion and exclusion criteria for lesson plans. Twenty-three papers were gained for the central paper review to answer the issue of this current study on how content knowledge aids prospective teachers in preparing lessons and what the challenges are. The findings indicate the development of lesson plans integrating knowledge teachers linked to pedagogy (i.e., teaching techniques, strategies, activities, and materials probably a connection to curricular knowledge), technology (digital tools, i.e., Kahoot, Quizlet), and students' knowledge (i.e., need, interest, and proficiency level). These findings paper highlighted teachers' knowledge, competence, and time management challenges. Still, these findings show that content knowledge is frequently marginalized or treated as a silent prerequisite rather than an active guiding force in lesson planning by only focusing on pedagogy and technology. This current study suggests CK must be reestablished as the guiding force behind instructional decision-making by emphasizing the need for in-depth research experience and knowledge for prospective English teachers.